THE PRINCIPLE OF HISTORICISM AND CONTINUITY IN SHAPING THE SPIRITUAL FOUNDATIONS OF NATIONAL IDEOLOGY (Eureka Journal of Humanities and Social Research, 2025)
The spiritual foundations of national ideology encompass the rich history, national traditions, values, customs, religious beliefs (Islam), national pride, language, moral principles, and universal values of the people. These elements contribute to the nation's self-awareness, unity, and development as an independent state.This article discusses the spiritual foundations of national ideology as well as the principles of historicism and continuity.
Keywords: National ideology, culture, spirituality, humanity, historicism, development, national formation, language, art, values, national idea, and security.